2013
DOI: 10.1186/1869-5760-3-62
|View full text |Cite
|
Sign up to set email alerts
|

Combined ceftazidime and amikacin resistance among Gram-negative isolates in acute-onset postoperative endophthalmitis: prevalence, antimicrobial susceptibilities, and visual acuity outcome

Abstract: BackgroundThe purpose of this study is to evaluate the prevalence, antimicrobial susceptibilities, and visual acuity outcome of acute-onset postoperative Gram-negative bacterial endophthalmitis cases resistant to both ceftazidime and amikacin seen between 2005 and 2010 at L. V. Prasad Eye Institute, a tertiary care ophthalmic Centre in South India. Medical records of all patients with Gram-negative bacterial endophthalmitis resistant to both amikacin and ceftazidime between 1 January 2005 and 31 December 2010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Jindal et al have reported 32/65 (49 %) GNB isolates from patients with acute onset post-operative endophthalmitis are resistant to ceftazidime [15]. The same groups of authors have reported 22 % of GNB isolated from patients with open globe injuries are resistant to ceftazidime [16].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Jindal et al have reported 32/65 (49 %) GNB isolates from patients with acute onset post-operative endophthalmitis are resistant to ceftazidime [15]. The same groups of authors have reported 22 % of GNB isolated from patients with open globe injuries are resistant to ceftazidime [16].…”
Section: Discussionmentioning
confidence: 87%
“…Five isolates of Pseudomonas species which are resistant to ceftazidime are susceptible to amikacin. Jindal et al have reported low resistant to amikacin (26 %) compared to ceftazidime (49 %) in GNB isolates [15]. Although there are reports on low resistance to amikacin compared to ceftazidime in GNB, intravitreal amikacin injection is associated with macular toxicity.…”
Section: Discussionmentioning
confidence: 96%
“…Jindal et al previously administered intravitreal imipenem for MDR P. aeruginosa , and Arora et al have now demonstrated intravitreal piperacillin-tazobactam as an alternative. 2,7 However, the poor outcomes in this latest outbreak unfortunately confirm that outcomes in these cases remain poor despite early and appropriate treatment.…”
Section: Letter To the Editormentioning
confidence: 91%
“…It acts by inhibiting cell wall synthesis of various Gram-positive and Gram-negative bacteria. It is stable to hydrolysis by the common plasmid-mediated β-lactamases produced by various bacteria and lacks cross-resistance with penicillins and third-generation cephalosporins 11. One case series reported use of intravitreal imipenem in the treatment of endophthalmitis caused by Acinetobacter baumannii .…”
Section: Discussionmentioning
confidence: 99%